Electrochemical evaluation of Re-doped SrFeO3-δ electrodes for SOFCs - Sánchez Caballero, Abraham; García-Plaza, Miguel Ángel; Porras-Vázquez, José Manuel; dos Santos-Gómez, Lucía; Zamudio-García, Javier; Marrero-López, David (My University, 2025)
Solid oxide fuel cells (SOFCs) offer high efficiency for clean energy conversion, but their high operating temperatures pose technical challenges. The development of symmetrical electrodes with improved electrochemical properties can enable more practical and cost-effective SOFC systems [1]. In this study, Sr0.95Fe1-xRexO3-δ (x = 0, 0.05, 0.1, 0.2, 0.3) perovskite-type materials were synthesized via the freeze-dried precursor method, aiming to enhance their structural stability and electronic conductivity under both oxidizing and reducing conditions. The electrodes were then deposited onto LSGM electrolytes using spray pyrolysis, ensuring uniform coverage and good adherence [2]. X-ray diffraction confirmed phase purity and the stabilization of the cubic structure with Re substitution. Scanning electron microscopy revealed reduced grain size with increased Re content. Electrochemical impedance spectroscopy showed that the composition with 20% Re offered the lowest polarization resistance and best overall performance. A single SOFC incorporating the Sr0.95Fe0.8Re0.2O3-δ electrode was fabricated and tested, demonstrating the suitability of this material for symmetrical SOFC operation.
Keywords: Pilas de combustible; Electroquímica; Symmetrical Solid Oxide Cell; SrFeO3; Nanocomposite; Freeze-drying; Perovskite